Isolation, characterization and decolorization of textile dyes by fungal isolates from textile effluents - Titilayo, Femi-Ola; Emmanuel, Adeyemi; Victor, Atere (International Journal of Biological Research, 2016)
Synthetic dyes have an adverse effect on the aquatic ecosystem and their toxic component has to be removed from the effluent before their exoneration. Microorganisms have the potentials to degrade complex and recalcitrant organic compounds into simpler fragments achieving complete mineralization. Thus, the aim of this work is to isolate and investigate the degradative potential of fungal isolates recovered from textile effluents. The fungal isolates encountered includes; Aspergillus niger (14.3 %), Aspergillus fumigatus (14.3 %), Cryptococcus sp. (28.6 %) and Candida albican (42.9 %). The fungal isolates utilized some selected synthetic dyes (Malachite green, Methylene blue, Eosin Y and Carbol fuchsine) as sole source of carbon and nitrogen. All the fungal isolates exhibited degradative and decolourization potential against the different dyes tested at varying degree. Highest decolourization (79.4%) was obtained by Aspergillus niger for Eosin Y dye, followed by Cryptococcus sp. (77.0%) for the same dye after five days incubation. However the least decolourization efficiency (35%) was obtained by Aspergillus fumigatus for Malachite green. The results have demonstrated the potential of the fungal isolates for the treatment of dye wastewater.